Traditional Marriage In Yoruba Culture: An Exploration Of Male Dominance - Olufunmilola Adekiitan Omotayo (Britain International for Academic Research (BIAR-Publisher), 2023)
This paper seeks to examine the structure of traditional marriage in the Yoruba culture and to explore how issues of bride price, virginity and fertility are used to reinforce male dominance. In the Yoruba culture, marriage is seen as a very important institution and it is regarded as a union between two families. Traditionally, the groom's family is responsible for providing a bride price to the bride's family. Bride price is seen as a bargaining chip, conferring rights to the husband to control the wife while also legitimizing her place in his family. Virginity is associated with purity and good character, with faithfulness to the husband being prerequisite for a good marriage. Fertility is seen as a duty of the wife and necessary for the continuity of the husband’s lineage. Failure to fulfil these roles was seen as grounds for divorce or repudiation. The paper adopts critical and reflective methods to explain male dominance as related to the issues of bride price, virginity and fertility in Yoruba traditional marriage and concludes that the traditional marriage practices that dictate these values are a source of inequality and oppression that reinforces male dominance in Yoruba society.